Self-sensing behavior and mechanical properties of carbon nanotubes/epoxy resin composite for asphalt pavement strain monitoring. (10th October 2020) - Xin, Xue; Liang, Ming; Yao, Zhanyong; Su, Linping; Zhang, Jizhe; Li, Peizhao; Sun, Changjun; Jiang, Hongguang
Highlights: A novel self-sensing strain sensor that can effectively detect micro-strain was prepared. Aligned CNTs lead to high sensitivity on strain variation for developed sensor. Proper content of CNTs is beneficial for the formation of conductive network. Abstract: The monitoring of pavement structure conditions, especially the parameters of strain, stress, etc, plays a crucial rule on the design, construction, service and maintenance of asphalt road. In recent years, sensing composite materials provide a new approach for technological innovation of strain sensors and the engineering structure monitoring, which can effectively adapt to complex construction and working environment. In this paper, aligned multiwall carbon nanotubes (MWCNTs) with excellent electrical conductivity of >1250 s/cm is used to prepare the epoxy matrix composites. The effect of varying percent of CNT on the mechanical, electrical, morphological and fatigue properties of epoxy/nanotube composites was evaluated. Based on these evaluations, a novel strain sensor that can effectively detect the strain range within 1000 and even 100 µɛ with high durability (more than 100, 000 cycles at 1000µɛ), repeatability and prompt response was developed for asphalt pavement strain monitoring. The results indicated that the best gauge factor of the developed sensor is up to 26.04, which is far higher than traditional metal strain sensors with gauge factor of 2. Mechanical properties of different stiffness can be adjusted by mixing CNTs amount, so as to accord with the modulus range of different pavement layer. Morphology analysis of CNT revealed that the variation of electrical resistance as a function of strain is mainly attributed to the deformation of 3D conductive structure, which is further affected by the variation of conductive path and tunnel conduction effect. Consequently, the results in the study provide a new pathway on the development of micro-strain monitoring sensors for asphalt pavement structure.